Pathophysiology and Therapeutics of Thoracic Aortic Aneurysm in Marfan Syndrome - Keiichi Asano; Anna Cantalupo; Lauriane Sedes; Francesco Ramirez (Biomolecules, 2022)
About 20% of individuals afflicted with thoracic aortic disease have single-gene mutations that predispose the vessel to aneurysm formation and/or acute aortic dissection often without associated syndromic features. One widely studied exception is Marfan syndrome (MFS) in which mutations in the extracellular protein fibrillin-1 cause additional abnormalities in the heart, eyes, and skeleton. Mouse models of MFS have been instrumental in delineating major cellular and molecular determinants of thoracic aortic disease. In spite of research efforts, translating experimental findings from MFS mice into effective drug therapies for MFS patients remains an unfulfilled promise. Here, we describe a series of studies that have implicated endothelial dysfunction and improper angiotensin II and TGFβ signaling in driving thoracic aortic disease in MFS mice. We also discuss how these investigations have influenced the way we conceptualized possible new therapies to slow down or even halt aneurysm progression in this relatively common connective tissue disorder.